2021
DOI: 10.21608/adjalexu.2021.165446
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myofibroblasts in the Primary Lesions and Lymph Node Metastasis of Oral Squamous Cell Carcinoma

Abstract: INTRODUCTION:Myofibroblasts are modified fibroblasts that express features of smooth muscle differentiation. These cells play a key role in physiologic and pathologic processes such as wound healing and tumorigenesis, respectively. Tumor cells work in close coordination with stromal elements from its stage of emergence to metastasis. Myofibroblasts are important stromal cells that play a crucial role in carcinogenesis due to its ability to modify the extracellular matrix. Alpha smooth muscle actin (α-SMA) is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Studies have shown that myofibroblasts are significantly expressed in OSCC tissues compared to normal controls, indicating their involvement in creating a permissive environment for cancer invasion 14 . Additionally, the presence of myofibroblasts has been linked to the progression and metastasis of OSCC, making them a potential marker for monitoring the disease's severity and development 15 . These activated myofibroblasts within the tumor microenvironment promote growth, invasion, and resistance to various therapies, ultimately impacting the prognosis of OSCC patients 16 .…”
Section: Role Of Myofibroblast In Oral Cancermentioning
confidence: 99%
“…Studies have shown that myofibroblasts are significantly expressed in OSCC tissues compared to normal controls, indicating their involvement in creating a permissive environment for cancer invasion 14 . Additionally, the presence of myofibroblasts has been linked to the progression and metastasis of OSCC, making them a potential marker for monitoring the disease's severity and development 15 . These activated myofibroblasts within the tumor microenvironment promote growth, invasion, and resistance to various therapies, ultimately impacting the prognosis of OSCC patients 16 .…”
Section: Role Of Myofibroblast In Oral Cancermentioning
confidence: 99%